ANALISIS STRUKTUR FISIK DAN STRUKTUR BATIN PADA LAGU GAYO “BERIJIN” - Saharani, Indah; Nuraina, Siti; Istiqamah, Istiqamah (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
Literature is a form of human ideas that can be embodied in beauty. The form of writing that is sung is called song lyrics. Gayo Land is known as an area that gave birth to many artists and writers. Gayo songs have been part of the life of the Gayo people since ancient times, because the inhabitants of this cool area really like to sing. The purpose of this study is to analyze more deeply the physical structure and inner structure of the Gayo song "Perijin". This research is a qualitative research with descriptive analysis method. Based on the analysis that has been carried out, the results show that the Gayo song is formed from two main elements, namely the physical structure and the inner structure. The physical structures in the Gayo song "permitted" include diction, imagery, figurative language, concrete words, and rhymes. While the inner structure contained in this song is the theme, tone, feeling, and message.